CUSTOMER VALUE SEBAGAI SUMBERDAYA INFORMASI BAGI PERUSAHAAN - Pujihastuti, Isti (Optimal: Jurnal Ekonomi dan Kewirausahaan, 2007)
Buy a product or services is a process and are influenced many factors. ext customers satisfaction. The concept of customer satisfaction suggests strong relationship to customer value in a hierarchical model Starting at the bottom of the hierarchy, customer learn to think about products and performances attribute. When purchasing and using a product, they learn concequence experiences, reflected in value in use and possession value, that is the next level up in the hierarchy. The top level, customer achieve their goals and purposes to attach goal- based satisfaction. Customer value is a customer?s perceived preference for and evaluation of those product attributes, attribute performances and consequences arising from use that facilitate (or block) achieving the customer?s goals and purposes in use situations. There are many information in a organization. Customer value is one of this information that is used to marketing decisition making. An organization need to form the customer?s value because that is influence the customer?s satisfaction. And the next, customer?s satisfaction will influence the buying-decision.